Quantifying dispersal variability among nearshore marine populations. Issue 10 (4th December 2020) - Catalano, Katrina A.; Dedrick, Allison G.; Stuart, Michelle R.; Puritz, Jonathan B.; Montes, Humberto R.; Pinsky, Malin L.
Abstract: Dispersal drives diverse processes from population persistence to community dynamics. However, the amount of temporal variation in dispersal and its consequences for metapopulation dynamics is largely unknown for organisms with environmentally driven dispersal (e.g., many marine larvae, arthropods and plant seeds). Here, we used genetic parentage analysis to detect larval dispersal events in a common coral reef fish, Amphiprion clarkii, along 30 km of coastline consisting of 19 reef patches in Ormoc Bay, Leyte, Philippines. We quantified variation in the dispersal kernel across seven years (2012–2018) and monsoon seasons with 71 parentage assignments from 791 recruits and 1, 729 adults. Connectivity patterns differed significantly among years and seasons in the scale and shape but not in the direction of dispersal. This interannual variation in dispersal kernels introduced positive temporal covariance among dispersal routes that theory predicts is likely to reduce stochastic metapopulation growth rates below the growth rates expected from only a single or a time‐averaged connectivity estimate. The extent of variation in mean dispersal distance observed here among years is comparable in magnitude to the differences across reef fish species. Considering dispersal variation will be an important avenue for further metapopulation and metacommunity research across diverse taxa. Abstract : see also the Perspective by Pablo Saenz Agudelo and Hugo Harrison.